PEMAHAMAN PERILAKU BELAJAR REMAJA TIONGHOA DALAM KONTEKS PENDIDIKAN - Ninawati , Ninawati; Afendi , Jelien; Angela , Mada; Theresia , Zeufania; Siswoto , Reynaldo Jerenimo (Provitae: Jurnal Psikologi Pendidikan, 2025)
This research aims to understand the learning behavior of Indonesian Chinese teenagers attending both public and private schools, using the Learning Behaviors Scale (LBS) as a measurement tool. Education is considered a fundamental necessity for humans, with significant impacts on a country's progress. Based on PISA data, the quality of education in Indonesia remains low, leading this research to focus on internal factors impacting learning outcomes, specifically the learning attitudes of Chinese teenagers. The normality test results indicate that the data used in this research have a normal distribution, strengthening the validity of the analysis conducted. Out of the 29 items in the LBS grouped into four dimensions—Attitude Towards Learning (AL), Competence Motivation (CM), Strategy/Flexibility (SF), and Attention/Persistence (AP)—only 18 items passed the reliability test. The use of LBS as a measurement tool to assess the learning attitudes of Indonesian Chinese teenagers will aid educators in crafting more comprehensive and efficient teaching strategies. Furthermore, this research compares its findings with previous research and identifies differences in factor groups that can provide new insights into the learning behavior of ethnic minority teenagers in Indonesia. Through its contributions to both theoretical and practical realms of educational psychology, this research is poised to significantly impact the development of teaching strategies attuned to the diverse ethnic backgrounds of Indonesian students.